Microsoft Internet information server 4 the complete reference - Mueller, John 1958- (Osborne McGraw-Hill, 1998)
Covers TCP/IP, ISAPI, MMC; ActiveX, MTS, OLE DB, DCOM. Includes configuring, monitoring, and troubleshooting and chapters on electronic commerce, security, and networking.